Chantal Mouffe vs. Carl Schmitt: The Political, Democracy, and the Question of Sovereignty - Smoleński, Jan (Hybris, 2012)
In this paper I compare political theories of Carl Schmitt and Chantal Mouffe in three important aspects - the conceptualization of the political, their attitude towards liberal democracy and the conception of political process - and point to significant discrepancies. Schmitt's concept of the political is deeply existential and essentially involves real possibility of death, whereas Mouffe's is more domesticated, centered around the struggle, not physical elimination. Schmitt sees liberal democracy as inherently contradictory, because it is grounded on contradictory principles: democratic equality and particularism, and liberal freedom and universalism. Mouffe perceives this contradiction as a locus of tension with emancipatory potential. I trace these differences to their different perception of history. Schmitt's vision of history is marked with ruptures created by the political emergencies, which correlates with his eventual, decisionistic conception of politics. Mouffe's processual conception of politics corresponds rather with the conception of the end of history.